Case Report: Three-Dimensional Printing–Assisted Surgical Treatment of Complex Body Vein Ectopic Drainage - Wei, Luyao; Sun, Guowen; Wu, Qin; Zhang, Weizhi; Tang, Mi; Zhao, Tianli; Hu, Shijun (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Complex ectopic drainage of body veins is a rare congenital disease. Its preoperative diagnosis and surgical choice can be considerable challenges. Case summary: A 5-year-old patient was diagnosed precisely by preoperative transthoracic echocardiography, computed tomography (CT), three-dimensional (3D) reconstruction, and three-dimensional (3D) printing of the heart and great blood vessels. The operation was performed successfully using flexible intraoperative intubation strategies. Conclusion: 3D printing technology can assist in the formulation of surgical protocols for complex body vein ectopic drainage. Flexible intubation strategies can increase the success of the operation.